THE IMPACT OF FLIPPED LEARNING 3.0 AND SELF REGULATED LEARNING TOWARD ELEVENTH GRADE STUDENTS’ SPEAKING PERFORMANCE - Mahendra, I Gusti Agung Bayu; Adnyani, Luh Diah Surya; Budiarta, Luh Gd Rahayu (Universitas Pendidikan Ganesha, 2020)
This study aimed to investigate the impact of flipped learning 3.0 and self-regulated learning on eleventh grade students’ speaking performance in SMA N 1 Sukasada. This study was quasi-experimental research. Forty-seven of eleventh grade students were the sample of this study that were divided into two groups by using cluster random sampling, namely experimental and control groups. The data were collected through a survey and post-test. The data were analyzed using a two-way ANOVA. The result showed that flipped learning 3.0 gave a significant difference on students’ speaking performance. Meanwhile, self-regulated learning did not give any significant differences on students’ speaking performance between those who had high and low self-regulated learning Moreover, there was no interaction effect between flipped learning 3.0 and self-regulated learning. Through the implementation of flipped learning 3.0 and self-regulated learning, the students were stimulated to learn independently. Thus, it creates their understanding and be active in the learning.